The Effect of Monitoring Card Utilization on Children’s Toothbrushing Compliance and OHI-S Status among Students - Eka Sri Rahayu; Syifa Aulia; Reca Reca; Henny Febriani; Wirza Wirza (Journal of Health Science and Medical Therapy, 2026)
Oral health is a fundamental component of overall human well-being, particularly among school-aged children who are highly vulnerable to dental and oral diseases due to limited knowledge, low awareness, and insufficient motivation to maintain proper oral hygiene. The Oral Hygiene Index-Simplified (OHI-S) is a widely used indicator to assess the level of oral cleanliness. One strategy to improve OHI-S status is the use of monitoring tools, such as a monitoring card, which functions as a systematic mechanism to observe and ensure adherence to planned health behaviors. This study aimed to examine the effect of monitoring card utilization on children’s toothbrushing compliance and OHI-S status among students of SDN 10 Panteriek, Lueng Bata District, Banda Aceh. This research employed a quasi-experimental design with a pretest–posttest non-equivalent control group approach. The study population consisted of all fourth-grade students (n = 46). The results demonstrated a statistically significant effect of monitoring card utilization on toothbrushing compliance and OHI-S status (p = 0.000; p < 0.05). These findings indicate that the integration of monitoring tools into oral health education interventions can effectively improve children’s oral hygiene behavior and outcomes. In conclusion, the use of monitoring cards significantly enhances children’s compliance with toothbrushing practices, which in turn leads to improved OHI-S status. It is recommended that students further develop their knowledge, behavior, and awareness regarding oral hygiene, while schools and families should support sustained behavioral change through structured monitoring and guidance. This study contributes to the growing body of evidence on school-based oral health promotion by demonstrating the effectiveness of monitoring cards as a simple, low-cost, and practical behavioral intervention to improve toothbrushing adherence and oral hygiene status among children. Furthermore, the findings provide valuable implications for the development of preventive oral health programs and support the integration of structured monitoring strategies involving both schools and families to foster long-term oral health behaviors and reduce the burden of dental and oral diseases in children.